Homozygous Autosomal Recessive DIAPH1 Mutation Associated with Central Nervous System Involvement and Aspergillosis: A Rare Case - Hossein Esmaeilzadeh; Rafat Noeiaghdam; Leila Johari; Seyed Ali Hosseini; Sayyed Hesamedin Nabavizadeh; Soheila Sadat Alyasin (Case Reports in Genetics)
The DIAPH1 gene fulfills critical immune and neurodevelopmental roles. It encodes the mammalian Diaphanous-related formin (mDia1) protein, which acts downstream of Rho GTPases to promote F-actin polymerization and stabilize microtubules. During mitosis, this protein is expressed in human neuronal precursor cells and considerably affects spindle formation and cell division. In humans, dominant gain-of-function DIAPH1 variants cause sensorineural deafness and macrothrombocytopenia (DFNA1), while homozygous DIAPH1 loss leads to seizures, cortical blindness, and microcephaly syndrome (SCBMS). To date, only 16 patients with SCBMS have been reported, none of whom were from Iran. Furthermore, aspergillosis is yet to be reported in patients with homozygous DIAPH1 loss, and the link between SCBMS and immunodeficiency remains elusive. In this study, we shed further light on this matter by reporting the clinical, genetic, and phenotypic characteristics of an Iranian boy with a long history of recurrent infections, diagnosed with SCBMS and immunodeficiency (NM_005219.5 c.3145C > T; p.R1049X variant) following aspergillosis and SARS-CoV-2 coinfection.